Oral Administration of Kefiran Induces Changes in the Balance of Immune Cells in a Murine Model - Medrano, Micaela (2011)
The aim of the present study was to evaluate the effect of the oral administration of kefiran on the balance of immune cells in a murine model. Six week old BALB/c mice were treated with kefiran (300 mg/L) for 0, 2 and 7 days. Kefiran treatment increased the number of IgA+ cells in lamina propria after 2 and 7 days. Percentage of B220+/MHCIIhigh cells in mesenteric lymph nodes (2 days) and Peyer's patches (7 days) was higher compared to untreated control mice. An increase of macrophages (F4/80+ cells) was observed in lamina propria and peritoneal cavity (2 and 7 days). In contrast, at day 7, macrophage population decreased in Peyer's patches. These results show the ability of kefiran to modify the balance of immune cells in intestinal mucosa. This property could be highly relevant for the comprehension of the probiotic effect attributed to kefir.